Avian Haemosporidian Parasites in Three Wild Columbids from Germany - Yvonne R. Schumm; Celine Frank; Uta Gerz; Hannes Ruß; Benjamin Metzger; Petra Quillfeldt (Microorganisms)
Birds are hosts to a diverse assemblage of vector-transmitted haemosporidian parasites. However, the true genetic diversity and many host–parasite interactions are still unknown, particularly in under-represented species groups such as wild doves and pigeons (Columbiformes). In this study, we examined the prevalence and lineage diversity of haemosporidian genera Plasmodium, Leucocytozoon, and Haemoproteus in three species of wild columbids, sampled in Germany. Examinations were performed by applying molecular methods (nested PCR and one-step multiplex PCR) and blood smear examination, and their respective advantages and disadvantages are discussed. In the case of the European Turtle Dove Streptopelia turtur, samples were collected along a west–east gradient throughout Germany, covering migratory birds from the Western and Central-Eastern flyway of this species. Although no infection was detected in the Stock Dove Columba oenas samples, 53% of Turtle Dove and 86% of Common Woodpigeon Columba palumbus harbored a parasite of at least one haemosporidian genus, revealing previously unknown lineage–host interactions. We were not able to demonstrate a correlation between infection status (presence or absence of infection based on PCR results) and parasitemia with condition based on the heterophil to lymphocyte ratio (H/L ratio). Neither lineage occurrence nor prevalence of infection followed any geographically specific patterns. Thus, haemosporidian lineages found in Turtle Doves could not be used as a marker of geographic origin that would allow the tracking of their nonbreeding distribution.